Keragaman Morfologi dan Seleksi Galur Harapan Terung (Solanum melongena L) Generasi F2 Tipe Pyriform - Muhafido Nafngi Huda; Elea Nur Aziza; Annisa Khoiriyah (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Eggplant (Solanum melongena L.) is an important horticultural crop with high economic value and broad morphological diversity, particularly in fruit traits. This study aimed to characterize the morphological diversity of an F2 eggplant population a Pyriform-fruited, evaluate phenotypic segregation based on qualitative traits, and identify promising lines for breeding programs. The study was conducted from November 2025 to March 2026 at the Teaching Factory Celeban Experimental Field, Politeknik Pembangunan Pertanian Yogyakarta Magelang, Yogyakarta, Indonesia. The plant materials consisted of 155 F2 individuals and three genotypes, TEV 01, TEV 02, and TB 412, used as references. Observations were conducted on 17 qualitative traits based on UPOV descriptors. Data were analyzed descriptively using frequency distributions and percentages, followed by UPGMA cluster analysis. The F2 population exhibited broad morphological diversity in vegetative, floral, and fruit traits. Dominant traits were Pyriform fruit shape (55%), dark purple fruit skin color (51%), spineless calyx (72%), absence of fruit grooves (55%), and straight fruit curvature (69%). Cluster analysis grouped the population into five major clusters at 70% similarity. Six promising lines were identified: 43-24, 48-8, 48-18, 92-5, 107-20, and 107-25. The F2 population has potential as a source of morphological diversity for further selection in developing superior eggplant varietiesTop of Form